Denosumab reduces early migration in total knee replacement: A randomized controlled trial involving 50 patients. (4th May 2017) - Ledin, Håkan; Good, Lars; Aspenberg, Per
Abstract : Background and purpose — Aseptic loosening is a main cause of late revision in total knee replacement (TKR). Migration of implants as measured by radiostereometric analysis (RSA) can predict future loosening. This migration is associated with bone resorption. Denosumab is a human monoclonal antibody that binds to receptors on osteoclast precursors and osteoclasts. This prevents osteoclast formation, resulting in less bone resorption in cortical and trabecular bone. We investigated whether denosumab can reduce migration of TKR, as measured with RSA. Patients and methods — In this 2-center, randomized, double-blind placebo-controlled trial, 50 patients with osteoarthritis of the knee were treated with an injection of either denosumab (60 mg) or placebo 1 day after knee replacement surgery and again after 6 months. RSA was performed postoperatively and after 6, 12, and 24 months. The primary effect variable was RSA maximal total point motion (MTPM) after 12 months. We also measured other RSA variables and the knee osteoarthritis outcome score (KOOS). Results — The primary effect variable, MTPM after 12 months, showed that migration in the denosumab group was statistically significantly less than in the controls. Denosumab MTPM 12 months was reduced by one-third (denosumab: median 0.24 mm, 10% and 90% percentiles: 0.15 and 0.41; placebo: median 0.36 mm, 10% and 90% percentiles: 0.20 and 0.62). The secondary MTPM variables (6 and 24 months) also showed a statistically significant reduction in migration. There was no significant difference in MTPM for the period 12–24 months. KOOS sub-variables were similiar between denosumab and placebo after 12 and 24 months. Interpretation — Denosumab reduces early migration in total knee replacement, as in previous trials using bisphosphonates. As migration is related to the risk of late loosening, denosumab may be beneficial for long-term results.